Interface for the factor-inclusion weighting approach in determining the number of multipath propagation clusters - Roque, Marielle Anne (Animo Repository, 2019)
Design and development of MIMO communication systems require a comprehensive analysis of channel characteristics. In real-world applications, the channel consists of randomly propagating signals that travel in two or more paths called multipaths. Literature shows an approach of analyzing the channel, which is knowing the number of clusters or groupings of these multipaths. This paper presents a development of an interface featuring a factor weighing approach in determining the number of clusters. Different visualizations and evaluation results are shown in the interface that allows users to visually compare and analyze the proposed method. Further, the paper shows the consistency of the results since it matches the analysis of the novel approach proposed by the authors. © 2019, World Academy of Research in Science and Engineering. All rights reserved.